Penyuluhan Tentang Efek Samping Bahan Kimia Sintesis Bagi Kesehatan - Fatmayati Fatmayati; Nina Veronika; Sri Wahyuni; Nur Asma Deli; Hanifah Khairiah (Politeknik Kampar, 2025)
The advancement of science and technology has led to various innovations, one of which is the production of synthetic chemicals widely used by industries and communities. Synthetic chemicals have a longer durability and more stable properties compared to natural chemicals; however, excessive use can negatively impact health. Society, especially housewives, needs to have adequate knowledge to use synthetic chemicals wisely, particularly in food products. In RT 09 – RW 08, Kelurahan Bangkinang, Kabupaten Kampar, the Community Service Team (PkM) from the Palm Processing Engineering Study Program, Politeknik Kampar, conducted a counseling and interactive discussion activity attended by 17 women members of the PKK Team. The method combined material delivery and discussion to enhance understanding of the effects of synthetic chemicals and their differences from organic chemicals. Evaluation results from questionnaires showed an increase in participants’ knowledge and awareness, as well as high enthusiasm to continue similar activities sustainably. This activity contributes to strengthening the role of mothers in creating healthy families through the safe and wise use of chemicals.